A process for identifying challenges and opportunities for outdoor recreation and tourism development using participatory workshops and big data - Zhang, Hongchao; Smith, Jordan W. (Frontiers in Sustainable Tourism, 2022)
The collaborative development of scientific and practical knowledge is fostered through processes which allow scientists and stakeholders to work together towards common interests and goals. The purpose of this community case study is to document a process by which big data characterizing the volume and spatial distribution of outdoor recreation and tourism behavior can be used to initiate collaborative discussions amongst the diverse stakeholders involved in outdoor recreation and tourism management. The process we document involves engaging a diverse group of stakeholders including public land managers, county and city government officials, and local business owners, in participatory workshops centered around visualizations of geotagged social media. We document how three workshops with outdoor recreation and tourism providers in Utah (USA) aided in the development of a shared understanding of the challenges and opportunities associated with meeting the growing demand for outdoor recreation and tourism opportunities.